(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This research aims to determine the effect of small sided games training on passing skills using the field experiment method. The population used was athletes from the SSB Bangau Putra Makassar Football Club. with a total sample of 40 people taken by proportional sampling. The data analysis technique used is the t-test at a significance level of 95%. The research results show that; (1) There is a significant influence of the form of small sided games training on ball passing skills in football games among SSB Club Bangau Men’s Athletes, proven t0 = 9.504 > tt = 2.137, and (2) There is a significant difference in influence between small sided games training and the control group on ball passing skills in football games among SSB Club Bangau Men’s Athletes, proven t0 = 2.475 > tt = 2.146.